Eliminating antibody polyreactivity through addition of N‐linked glycosylation. (12th May 2015) - Chuang, Gwo‐Yu; Zhang, Baoshan; McKee, Krisha; O'Dell, Sijy; Kwon, Young Do; Zhou, Tongqing; Blinn, Julie; Lloyd, Krissey; Parks, Robert; Von Holle, Tarra; Ko, Sung‐Youl; Kong, Wing‐Pui; et al.
ABSTRACT Antibody polyreactivity can be an obstacle to translating a candidate antibody into a clinical product. Standard tests such as antibody binding to cardiolipin, HEp‐2 cells, or nuclear antigens provide measures of polyreactivity, but its causes and the means to resolve are often unclear. Here we present a method for eliminating antibody polyreactivity through the computational design and genetic addition of N‐linked glycosylation near known sites of polyreactivity. We used the HIV‐1‐neutralizing antibody, VRC07, as a test case, since efforts to increase VRC07 potency at three spatially distinct sites resulted in enhanced polyreactivity. The addition of N‐linked glycans proximal to the polyreactivity‐enhancing mutations at each of the spatially distinct sites resulted in reduced antibody polyreactivity as measured by (i) anti‐cardiolipin ELISA, (ii) Luminex AtheNA Multi‐Lyte ANA binding, and (iii) HEp‐2 cell staining. The reduced polyreactivity trended with increased antibody concentration over time in mice, but not with improved overall protein stability as measured by differential scanning calorimetry. Moreover, glycan proximity to the site of polyreactivity appeared to be a critical factor. The results provide evidence that antibody polyreactivity can result from local, rather than global, features of an antibody and that addition of N‐linked glycosylation can be an effective approach to reducing antibody polyreactivity.